Analisis Tentang Konsep Dasar Pendidikan Islam (Perspektif Al- Hadits) - Azzahra, Intan Nuraini; Azzahra, Mutia; Ragil, Almer; Wismanto, Wismanto (STAI Denpasar Bali, 2024)
This article attempts to highlight the basic foundations or concepts of Islamic education contained in the Koran and Hadith. The basic concepts of Islamic education that can be found in the Hadith are: First, the object of education is Adam or humans. Second is Islamic education material. Third is the teaching method. Fourth is the value or benefits of education. Fifth, studying is an obligation. The aim of this research is to reveal the basic conceptual model of Islamic education from a hadith perspective. The method used in this research is a qualitative method with a library research approach. This method makes books, magazines and the latest articles related to this research theme as the main source of research. The results of this research show that the method of explaining Islamic religious education is explained in various ways, including the hadith which discusses the object of education, Islamic education materials, teaching methods, the value or benefits of education, and the obligation to study.